2018
DOI: 10.1371/journal.pone.0195560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraoperative touch imprint cytology on axillary sentinel lymph nodes in invasive breast carcinomas, a retrospective study of 1227 patients comparing sensitivity in the different tumor subtypes

Abstract: BackgroundIntraoperative evaluation of the axillary sentinel lymph node (SLN) in patients with breast carcinoma reduces the need of re-operations in cases where an axillary completion lymph node dissection (CLND) is indicated. Different methods have been used to determine the SLN status intraoperatively, e.g. frozen section histology (FS) and touch imprint cytology (TIC). The sensitivity of intraoperative TIC examination on SLN is not consistent between different studies and varies according to different tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…In particular, invasive lobular carcinoma may be the most difficult tumor to diagnose, as the size and shape of lymphoid and tumor cells may be very similar. In our study, all cases were ductal carcinomas, although Pétursson et al [15] reported no differences in TIC sensitivity between different histological subtypes. As mentioned above, the false-negative cases represented micrometastases or isolated tumor cells, and the importance of these findings is still under much debate.…”
Section: Discussioncontrasting
confidence: 55%
“…In particular, invasive lobular carcinoma may be the most difficult tumor to diagnose, as the size and shape of lymphoid and tumor cells may be very similar. In our study, all cases were ductal carcinomas, although Pétursson et al [15] reported no differences in TIC sensitivity between different histological subtypes. As mentioned above, the false-negative cases represented micrometastases or isolated tumor cells, and the importance of these findings is still under much debate.…”
Section: Discussioncontrasting
confidence: 55%
“…Pétursson et al found TIC to be highly specific and moderately sensitive for the detection of breast cancer, and interestingly, the sensitivity improved over years, which suggests that implementing TIC in routine settings will increase the overall detection rates and decrease false-negative results over time. The study also concluded that there were no differences in the sensitivity of TIC for different subtypes of breast cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the aim of finding a cost-effective and beneficial intervention for fast evaluation of cancer cells, several on-site techniques have been evaluated [9, 18]. However, weak sensitivity and limited clinical practicability were the main deficits so far [10, 19, 20]. Previous publications documented a high image resolution by confocal microscope scanning, providing a visualization of cellular details equal to H&E standard [13–15].…”
Section: Discussionmentioning
confidence: 99%